ANALYSIS OF STUDENTS MENTAL MODELS THROUGH POE (PREDICT OBSERVE EXPLAIN) METHOD IN SALT HYDROLISIS TOPIC - Kiswandari Kiswandari; Achmad Ridwan (Jurnal Tadris Kimiya, 2020)
This study aimed to analyze students mental models in salt hydrolysis topic using POE method (Predict Observe Explain) to determine students understanding of salt hydrolysis topic. The research method used  descriptive qualitative approach. Data collection used diagnostic tests of mental models, observation, reflective journals and semi-structured interviews on samples of respondents of students class XI.  The result showed that 3.88% of respondents had a Specific Misconceptions (SM) mental model, 7.9% Partially Correct (PC) and 88.146% Scientifically Correct (SC). It can be concluded that the majority of respondents have scientifically correct mental models and show themes which appeared at each macroscopic, symbolic and microscopic.